Neoplatonism and Indian thought - Harris, R. Baine, 1927- (Studies in Neoplatonism ;, 1982)
Papers presented at an international conference held at Brock University, St. Catharines, Ontario, Canada in October, 1976; sponsored jointly by Brock University and the International Society for Neoplatonic Studies. Includes bibliographical references and index.